(untitled) (Research, Society and Development, 2020)
This study aims to analyze the organizational climate and job satisfaction in a supermarket. Methodologically, it is a qualitative research that consists of a survey study with the employees of the studied company. Data collection took place through on-the-spot interviews that raised questions about motivation, interests, satisfaction in the company and among other aspects. The results showed a considerably good degree of satisfaction, where many of the employees’ expectations are met. In general, the study concludes that the organizational climate and satisfaction with the supermarket’s work are adequate.